Social media and its impact on academic performance among university students - Al-Rahmi, Waleed Mugahed; Zeki, Akram M.; Alias, Norma; Saged, Ali Ali (Kamla-Raj Enterprises, 2017)
Social media has been suggested as an effective tool for the educational purpose. Therefore, this study is conducted on two theories, constructivism theory and Technology Acceptance Model (TAM). Moreover, this study conducted an analysis of studies dedicated to social media use for collaborative learning and engagement based on previous research problems of models and theories. In addition, this study applied quantitative approach, and the questionnaire was conducted using 340 students. The results show that social media use is useful, enjoyable and easy to use. Moreover, the students had a feeling of satisfaction using it. They believe that social media can be used positively and that it can provide significant interaction, engagement, and collaborative learning with respect to the Quran and Hadith, thus improving learners' performance. The results of this study also revealed the percentage and frequency of the tools of social media used for collaborative learning, sharing, discussion, and publishing.